The Bremen town musicians - Johnson, David 1951 February 18- ([Edina, Minn.] : ABDO Pub. Co., 2005)
A retelling of the Grimm tale in which an old donkey, dog, cat, and rooster, no longer wanted by their masters, set out for Bremen to become musicians.
"Rabbit Ears books."
"Rabbit Ears, a classic tale"--Cover.
Accelerated Reader AR
106418
Keywords: Grimm, Jacob -- 1785-1863 -- Adaptations -- Juvenile literature; Grimm, Wilhelm -- 1786-1859 -- Adaptations -- Juvenile literature; Fairy tales; Folklore -- Germany; Fairy tales